2018
DOI: 10.3390/cells7050036
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species, Superoxide Dimutases, and PTEN-p53-AKT-MDM2 Signaling Loop Network in Mesenchymal Stem/Stromal Cells Regulation

Abstract: Mesenchymal stromal/stem cells (MSCs) are multipotent cells that can differentiate to various specialized cells, which have the potential capacity to differentiate properly and accelerate recovery in damaged sites of the body. This stem cell technology has become the fundamental element in regenerative medicine. As reactive oxygen species (ROS) have been reported to adversely influence stem cell properties, it is imperative to attenuate the extent of ROS to the promising protective approach with MSCs’ regenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 84 publications
(90 reference statements)
0
49
0
Order By: Relevance
“…Western blot results showed the same change ( Figure 2B). Then, we examined the expression of p53 and p21 during the replicative senescence of mBMSCs by continuous long-term passage [15] and found that p53 and p21 were signi cantly increased after passage 20 (P20) compared with the early phase passage 5 (P5) ( Figure 2C, 2D). It is possible to conclude that p53 and p21 were upregulated in the process of cellular senescence induced by H 2 O 2 or serial passage.…”
Section: Resultsmentioning
confidence: 99%
“…Western blot results showed the same change ( Figure 2B). Then, we examined the expression of p53 and p21 during the replicative senescence of mBMSCs by continuous long-term passage [15] and found that p53 and p21 were signi cantly increased after passage 20 (P20) compared with the early phase passage 5 (P5) ( Figure 2C, 2D). It is possible to conclude that p53 and p21 were upregulated in the process of cellular senescence induced by H 2 O 2 or serial passage.…”
Section: Resultsmentioning
confidence: 99%
“…While free radicals have been reported crucial for normal biology of stem cells, excessive ROS (oxidative stress) adversely influence the stem cell properties and cell therapy outcome (Matsuda, Nakagawa, Kitagishi, Nakanishi, & Murai, 2018). Therefore, it is imperative to control the extent of ROS to have a promising regenerative therapy in damaged tissue linked to hypoxia and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is imperative to control the extent of ROS to have a promising regenerative therapy in damaged tissue linked to hypoxia and oxidative stress. Additionally, oxidative stress can affect stem cell expansion and longevity (Matsuda et al, 2018). Moreover, it may be possible to control MSCs' fate in vitro and in vivo by regulating the ROS levels surrounding MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…MAPK, is an important mediator responsive to extracellular stressors [46] [47] [48]. The fact that p38 MAPK is involved in the molecular interaction during aging indicates that p53 is a major mediator of ROS-related signal transduction.…”
Section: Impact Of Stem Cell Senescence In Aging and Diseasesmentioning
confidence: 99%